2022
DOI: 10.5194/tc-2022-192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating surface melt in Antarctica from 1979 to 2022, using a statistically parameterized positive degree-day model

Abstract: Abstract. Surface melt is one of the primary drivers of ice shelf collapse in Antarctica. Surface melting is expected to increase in the future as the global climate continues to warm, because there is a statistically significant positive relationship between air temperature and melt. Enhanced surface melt will negatively impact the mass balance of the Antarctic Ice Sheet (AIS) and, through dynamic feedbacks, induce changes in global mean sea level (GMSL). However, current understanding of surface melt in Anta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…5a). Additionally, we do not observe a close association between monthly Positive Degree Days (PDDsa measure of above-freezing air temperatures) and surface meltwater area, consistent with research that found no trend in EAIS surface melting over recent decades 34 . On a multi-annual scale, therefore, there is no clear climatic driver for the increasing trend in EAIS meltwater area.…”
Section: Links With Antarctic Climatesupporting
confidence: 90%
“…5a). Additionally, we do not observe a close association between monthly Positive Degree Days (PDDsa measure of above-freezing air temperatures) and surface meltwater area, consistent with research that found no trend in EAIS surface melting over recent decades 34 . On a multi-annual scale, therefore, there is no clear climatic driver for the increasing trend in EAIS meltwater area.…”
Section: Links With Antarctic Climatesupporting
confidence: 90%
“…The two-sample KS test evaluates the distance between the empirical distribution functions derived from two different samples of data (Lanzante 2021;Moustakis et al 2022). Given its nonparametric nature, this method avoids assumptions about the distribution of the samples (Zheng et al 2022).…”
Section: Prioritizing the Importance Of Ppbsmentioning
confidence: 99%
“…This melting dataset provides the daily status of dry and wet snow at each grid pixel within the range, which is used to detect the days and regions where melting occurred. They are determined by the different dielectric constants of dry and wet snow, distinguished by the variation of upwelling microwave brightness temperature [52]. This dataset spans from April 1979 to March 2021 and has a spatial resolution of 25 km with a stereographic polar grid.…”
Section: Surface Melting Daysmentioning
confidence: 99%